(3cJGH aj GdHjRQIs
(3ChdgG (B:s
(3jJOF HCKfGA GdcdGe Ydi GdagO hNUGFUg Hbhdg (B( (3ef GdeTGjN GdUQGA Hge GdPjf dge QCi UMjM jbhdhf Cfge jYQahf HQcI GdagO SGYI jONd OGQ GdQLd s
(3BNQgG (B:s
(3hCeG GdPi jfaYg adMe GdZRGd LjO jfaY GdLSe EdG Cfg EPG OGheg GdHGRi NeSI CjGe s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs